Fostering Religious Education for Transformation in Indonesia: Dialogue with Transformative Learning Theory - Alexander Hendra Dwi Asmara (P3TK, Sanata Dharma University, 2020)
This essay attempts to construct a model of religious education for transformation that effectively addresses the growth of everyday religious conflict in Indonesias post-Suharto era. Using the lens of transformative learning theory, this essay emphasizes that the task of religious education should not merely serve as an intra-ecclesial agency of church or religious maintenance but must retrieve its task to reconstruct and to transform social situations. Such a vision emphasizes the task of religious educators to inform and form people to bring them into the fullness of life for themselves and others to transform the world. This essay draws insights from two scholars in transformative learning theory Jack Mezirow and Paulo Freire who point out two foundations for transformation: (1) critical reflection, and (2) dialogue. These two visions can inspire religious educators to introduce critical reflection in their curriculum and to develop interreligious education that nurtures dialogue and collaboration. By focusing on developing critical reflection and interreligious education, religious education can offer transformation in Indonesian society plagued by ongoing conflict.